From the History of Criminalistics: Antonio Maria Cospi (1560–1635) - Sh. N. Khaziev (Теория и практика судебной экспертизы, 2024)
When describing the history of modern forensic science and practice, the vast majority of scientific and educational publications deservedly note the crucial role of the Austrian forensic investigator and Professor Hans Gross, who wrote and published «Guide for forensic investigators as a system of forensic science» in 1893. However, long before Hans Gross, a book by the Florentine criminal judge Antonio Maria Cospi, «The Judge-Criminalist», was published in Italy in 1643. In some Latin American and Italian publications devoted to the history of criminalistics, there are references to this book, but no descriptions of its contents or information about the author are given. This article makes an attempt to pay tribute to Kospi’s contribution to the formation and development of criminalistics.